Mammaglobin immunostaining in the differential diagnosis between cutaneous apocrine carcinoma and cutaneous metastasis from breast carcinoma - Fernandez-Flores, A (Ceskoslovenska patologie, 2009)
The differential diagnosis between cutaneous apocrine carcinoma (CAC) and cutaneous metastases from breast carcinoma is commonly difficult. Many times, clinical information is crucial in the final diagnosis, because help that can be obtained from immunohistochemistry is usually limited concerning this subject. We used the antibody mammaglobin in order to study 10 cases of cutaneous metastasis of ductal breast carcinoma, and 2 cases of CAC. One of the CAC cases showed only scattered positive cells, while the other did not show any positivity. Four cases of metastatic breast carcinoma also showed scattered positive cells. In other five metastatic cases, positive cells were abundant, representing up to 60% of the tumoral cells. One case of metastatic breast carcinoma did not show any expression of mammaglobin at all. Although, more cases of CAC should probably be studied in the future before any categorical conclusion can be obtained, our results seem to indicate that a pattern of immunostaining with expression of mammaglobin in many cells would favor a metastatic origin of the tumor.
Keywords: senioři; diferenciální diagnóza; Neoplasm Proteins; Breast Neoplasms; senioři nad 80 let; apokrinní žlázy; nádorové proteiny; Skin Neoplasms; Middle Aged; Adult; Apocrine Glands; uteroglobin; mammaglobin A; Biomarkers, Tumor; Aged, 80 and over; Sweat Gland Neoplasms; ženské pohlaví; nádorové biomarkery; Humans; nádory kůže; lidé středního věku; Uteroglobin; Diagnosis, Differential; nádory prsu; dospělí; nádory potních žláz; Female; Aged; Mammaglobin A; lidé